Pengaruh Senam Yoga dan Aromaterapi Clary Sage terhadap Penurunan Skala Nyeri Dismenore Kelas XI dan XII di SMA Unggulan Nurul Islami Semarang - Dilma Rochmi Ashina Sarma; Agnes Istiharjanti; Mudy Oktiningrum (Jurnal Rumpun Ilmu Kesehatan, 2025)
Non-pharmacological therapies for managing dysmenorrhea include yoga exercises and clary sage aromatherapy. This pre-experimental research determined the effect of yoga exercises and clary sage aromatherapy to relieve dysmenorrhea pain scale among 11th and 12th-graders at Advanced High School Nurul Islami Semarang with a one-group pretest-posttest design. The population in this study consists of students from the XI and XII grades of Advanced High School Nurul Islami Semarang, 70 students, with a research sample of 42 respondents. The data collection technique for this research was purposive sampling. The numeric rating scale serves as the measuring tool. The statistical test conducted before and after yoga exercises and clary sage aromatherapy in this study is the Wilcoxon test, obtaining a p-value of 0.000 < 0.05. The result accepts the alternative hypothesis (Ha). This indicates that yoga exercises and clary sage aromatherapy relieve dysmenorrhea pain in 11th and 12th graders at Advanced High School Nurul Islami Semarang. The conclusion is that yoga exercises and clary sage aromatherapy have an impact on reducing dysmenorrhea.